THE IMPACT OF BALANCED ENERGY AND PROTEIN SUPPLEMENTATION TO MILK PRODUCTION AND QUALITY IN EARLY LACTATING DAIRY COWS - Widyobroto, W. P.; Rochijan, R.; Ismaya, I.; Adiarto, A.; Suranindyah, Y. Y. (Diponegoro University, 2016)
This research was aimed to determine the impact of balanced energy and protein supplementation with high rumen undegraded protein (HRUP) to milk production and quality in early lactating dairy cows. Twelve early lactating Friesian Holstein cows were divided into two groups (control and HRUP). Both control and HRUP group were fed on a basal diet (forage to concentrate ratio was 60:40; DM basis), with rumen undegraded protein (RUP) levels were 27.47% and 32.78% for control and HRUP, respectively. The experimental diets were given to animals twice daily, morning and afternoon. Water was given by ad libitum. The observed parameters were nutrient intake, quantity and quality of milk production . Data were examined using t-test. Results showed that feed intake, milk production and 4% FCM, milk fat and lactose concentrations, and milk solid non-fat and total solid concentrations were not differed significantly between control and HRUP groups. However, milk protein concentration and production were differed (P